Experimental assessment of turtle predation on larval anurans - Gómez-Mestre, Iván; Keller, Claudia (Copeia, 2003)
The effect of predation by large non-gape-limited vertebrates on the survivorship and size distribution of larvae of four anuran species was assessed using two syntopic freshwater turtle species, Emys orbicularis and Mauremys leprosa. Predator species and predator sex within species were used as treatments in replicated, factorial experiments for predation trials on tadpoles of Bufo calamita, Hyla meridionalis, Rana perezi, and Pelobates cultripes. Tadpole consumption rates were significantly higher for the carnivorous E. orbicularis than for M. leprosa. Rana perezi tadpoles were the least consumed, whereas P. cultripes and H. meridionalis had the lowest survivorship rates, being relatively easier to catch than R. perezi. Significant size selection occured for larger tadpoles of P. cultripes, whereas predation upon R. perezi tended to concentrate on the smaller size classes. The results point to an overall tendency of turtles to predate upon large tadpoles, yet the outcome of size selection by large vertebrates may depend on phenotypic traits that enhance the escape potential of tadoles. Mauremys leprosa had a high rejection rate of tadpoles, suggesting a higher sensitivity to unpalatability as compared to E. orbicularis, especially with relation to R. perezi. The results indicate that the effect of unpalatability as a predation deterrent may vary even among taxonomically close predator species.
Keywords: Amphibian; Palatability; Predator-prey Interaction; Prey Size; Size Distribution; Survivorship; Turtle; Amphibia; Anura; Bufo; Bufo Calamita; Bufo Calamita; Emys; Emys Orbicularis; Emys Orbicularis; Hyla; Hyla Meridionalis; Hyla Meridionalis; Mauremys; Mauremys Leprosa; Mauremys Leprosa; Pelobates; Pelobates Cultripes; Pelobates Cultripes; Rana Perezi; Rana Perezi; Reptilia; Testudines; Vertebrata